A Role for MK2 in Enhancing Neutrophil-Derived ROS Production and Aggravating Liver Ischemia/Reperfusion Injury - Sun, Lei; Wu, Qiong; Nie, Yunjuan; Cheng, Ni; Wang, Rui; Wang, Gang; Zhang, Dan; He, Huiqiong; Ye, Richard D.; Qian, Feng (Frontiers in Immunology, 2018)
Increased inflammatory responses and enhanced reactive oxygen species contribute to hepatic ischemia/reperfusion (I/R) injury, however the modulatory mechanisms haven't been completely unveiled. Here, we report that genetic deficiency of MAPK-activated protein kinase 2 (MK2) protected against hepatic I/R injury and decreased hepatic neutrophil accumulation in MK2−/− mice. Depletion of neutrophil attenuated hepatic I/R injury in wide type mice. In response to C5a stimulation, MK2−/− neutrophils generated less superoxide in which both NADPH oxidase activation and p47phox phosphorylation were decreased. Furthermore, Ser329 of p47phox was identified for enhancement of superoxide production. The Ser329 phosphorylation was reduced in MK2−/− neutrophils. To determine whether MK2 modulates hepatic I/R injury via activating neutrophils, we generated myeloid-specific MK2 deletion mice (MK2Lyz2−KO) and liver I/R injury was reduced in MK2Lyz2−KO mice. Our results indicate that MK2 augments hepatic I/R injury and induces ROS production with increased p47phox phosphorylation and MK2 is a potential drug target for treating hepatic I/R injury.